Enhanced Effect of the Mesoporous Carbon on Iron Carbide Catalyst for Hydrogenation of Dimethyl Oxalate to Ethanol. Issue 20 (6th July 2022) - Cao, Meng; Huang, Huijiang; Zheng, Yuntao; Zhang, Qiaochu; Wang, Shengping; Ge, Rile; Wang, Junhu; Zhao, Yujun; Ma, Xinbin
Abstract: Due to the low activity of bulk Fe5 C2 catalyst in the hydrogenation of dimethyl oxalate to ethanol, a supported Fe5 C2 catalyst was designed and prepared with mesoporous carbon as the carrier. For a comparison, two iron carbide catalysts supported on activated carbon and microporous carbon were also prepared. Based on the characterization results of IR, XRD, H2 ‐TPR, CO‐TPD, XPS and MES, the oxygen‐containing functional groups (especially COOH group) on the surface of the carbon supports inhibit the formation of iron carbides, which are regarded as the active sites and play the key role in the hydrogenation of dimethyl oxalate to ethanol. However, the mesoporous carbon exhibits a more positive effect on the dispersion of iron particles than the other two carbon supports. As a result, the as‐prepared mesoporous catalyst presents an excellent activity (the ethanol yield of 85.8 %) and stability in the hydrogenation of dimethyl oxalate. This work suggests a practical strategy in fabricating a supported iron carbides catalyst for the chemosynthesis of ethanol via DMO hydrogenation from syngas. Abstract : Supported catalysts : The mesoporous structure improves the dispersion of iron particles and enhances the formation of more available active sites. As a result, the catalyst presents an excellent activity and stability in the hydrogenation of dimethyl oxalate to ethanol than the catalyst supported on microporous carbon.